2011
DOI: 10.1007/s10695-011-9476-1
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility complex class IIA and IIB genes of the spotted halibut Verasper variegatus: genomic structure, molecular polymorphism, and expression analysis

Abstract: The major histocompatibility complex (MHC) is a large genomic region characterized by extremely high polymorphism and its association with resistance/susceptibility to disease in vertebrates. In this study, the full lengths of MHC IIA and IIB cDNA were obtained from spotted halibut (Verasper variegates) by expressed sequence tag (EST) and rapid amplification of cDNA ends (RACE) approaches. The genomic structure, molecular polymorphism, and expression patterns were examined to study MHC II gene functions in fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…We showed that the complete genomic sequence of swamp eel MHC IIA consists of four exons and three introns, and is similar to that of the turbot (Zhang & Chen 2006a), spotted halibut (Li et al 2011), Mi-iuy croaker and Nile tilapia (Pang et al 2013). Alignment analysis showed that the MHC IIA gene shares high degree of similarity to that of other vertebrates.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…We showed that the complete genomic sequence of swamp eel MHC IIA consists of four exons and three introns, and is similar to that of the turbot (Zhang & Chen 2006a), spotted halibut (Li et al 2011), Mi-iuy croaker and Nile tilapia (Pang et al 2013). Alignment analysis showed that the MHC IIA gene shares high degree of similarity to that of other vertebrates.…”
Section: Discussionmentioning
confidence: 80%
“…Further analysis showed that five different 5' UTR sequences and two different 3' UTR sequences could also be found from a single individual, implying the existence of five loci at least. Different class IIA numbers have been also found in other fish species, such as two loci have been identified in both half-smooth tongue sole (Xu et al 2009) and spotted halibut (Li et al 2011). More than four MHC IIA alleles were identified in a single individual suggested the existence of at least four loci in Nile tilapia (Pang et al 2013).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations